# Class 11 RD Sharma Solutions – Chapter 12 Mathematical Induction – Exercise 12.2 | Set 1

### Prove the following by the principle of mathematical induction:

### Question 1. 1 + 2 + 3 + â€¦ + n = n (n +1)/2 i.e., the sum of the first n natural numbers is n (n + 1)/2.

**Solution:**

Let, P (n) = 1 + 2 + 3 + â€¦.. + n = n (n +1)/2.

Step 1:

Now, let us check P(n) for n = 1.

So, P (1) = 1 (1 + 1)/2 = 1.

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

Then, 1 + 2 + 3 + â€¦. + k = k (k + 1)/2 … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

(1 + 2 + 3 + â€¦ + k) + (k + 1) = k (k + 1)/2 + (k + 1)

= (k + 1) (k/2 + 1)

= [(k + 1) (k + 2)] / 2

= [(k + 1) [(k + 1) + 1]] / 2

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI) P (n) is true for all n âˆˆ N.

### Question 2. 1^{2} + 2^{2} + 3^{2} + â€¦ + n^{2} = [n (n + 1) (2n + 1)]/6

**Solution:**

Let, P (n) = 1

^{2}+ 2^{2}+ 3^{2}+ â€¦ + n^{2}= [n (n + 1) (2n + 1)]/6Step 1:

Now, let us check P(n) for n = 1.

So, P (1) = [1 (1 + 1) (2 + 1)]/6

or, 1 = 1.

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

Then, 1

^{2}+ 2^{2}+ 3^{2}+ â€¦ + k^{2}= [k (k + 1) (2k + 1)]/6Step 3:

Now, we have to prove for P(k + 1) is true.

P (k) = 1

^{2}+ 2^{2}+ 3^{2}+ …….. + k^{2}+ (k + 1)^{2}= [k + 1 (k + 2) (2k + 3)] /6= 1

^{2}+ 2^{2}+ 3^{2}+ ……. + k^{2}+ (k + 1)^{2}= [k + 1 (k + 2) (2k + 3)] /6 + (k + 1)

^{2}= (k +1) [(2k

^{2}+ k)/6 + (k + 1)/1]= (k +1) [2k

^{2}+ k + 6k + 6]/6= (k +1) [2k

^{2}+ 7k + 6]/6= (k +1) [2k

^{2}+ 4k + 3k + 6]/6= (k +1) [2k(k + 2) + 3(k + 2)]/6

= [(k +1) (2k + 3) (k + 2)] / 6

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 3. 1 + 3 + 3^{2} + â€¦ + 3n – 1 = (3n â€“ 1)/2

**Solution:**

Let P (n) = 1 + 3 + 3

^{2}+ ……. + 3n â€“ 1 = (3n â€“ 1)/2Step 1:

Now, let us check P(n) for n=1.

P (1) = 1 = (3(1) â€“ 1)/2 = (3 â€“ 1)/2 = 2/2 =1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 + 3 + 3

^{2}+ ……. + 3k â€“ 1 = (3k â€“ 1)/2 â€¦ (i)Step 3:

Now, we have to prove for P(k + 1) is true.

Then,

{1 + 3 + 3

^{2}+ ……. + 3k â€“ 1} + 3k + 1 â€“ 1Using equation (i), we get

= (3k â€“ 1)/2 + 3k

= (3k â€“ 1 + 2 Ã— 3k)/2

= (3 Ã— 3 k â€“ 1)/2

= (3

^{k + 1 }â€“ 1)/2So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 4. 1/1.2 + 1/2.3 + 1/3.4 + â€¦ + 1/n(n + 1) = n/(n + 1)

**Solution:**

Let P (n) = 1/1.2 + 1/2.3 + 1/3.4 + â€¦ + 1/n(n + 1) = n/(n + 1)

Step 1:

Now, let us check P(n) for n=1.

P (1) = 1/1.2 = 1/(1 + 1)

1/2 = 1/2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 /1.2 + 1/2.3 + 1/3.4 + â€¦ + 1/k(k + 1) + k/(k + 1) (k + 2) = (k + 1)/(k + 2) â€¦ (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then,

1/1.2 + 1/2.3 + 1/3.4 + â€¦ + 1/k(k + 1) + k/(k + 1) (k + 2)

= 1/(k + 1)/(k + 2) + k/(k + 1)

= 1/(k + 1) [k(k + 2)+1]/(k + 2)

= 1/(k + 1) [k

^{2}+ 2k + 1]/(k + 2)=1/(k + 1) [(k + 1) (k + 1)]/(k + 2)

= (k + 1) / (k + 2)

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 5. 1 + 3 + 5 + â€¦ + (2n â€“ 1) = n^{2} i.e., the sum of first n odd natural numbers is n^{2}.

**Solution:**

Let P (n) = 1 + 3 + 5 + â€¦ + (2n â€“ 1) = n

^{2}Step 1:

Now, let us check P(n) for n=1.

P (1) = 1 = 1

^{2 }= 1So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 + 3 + 5 + â€¦ + (2k â€“ 1) = k

^{2}â€¦ (i)Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1 + 3 + 5 + â€¦ + (2k â€“ 1) + 2(k + 1) â€“ 1

= k

^{2}+ (2k + 1)= k

^{2}+ 2k + 1= (k + 1)

^{2}So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 6. 1/2.5 + 1/5.8 + 1/8.11 + â€¦ + 1/(3n – 1) (3n + 2) = n/(6n + 4)

**Solution:**

Let P (n) = 1/2.5 + 1/5.8 + 1/8.11 + â€¦ + 1/(3n – 1) (3n + 2) = n/(6n + 4)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/2.5 = 1/(6.1 + 4)

or, 1/10 = 1/10

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1/2.5 + 1/5.8 + 1/8.11 + â€¦ + 1/(3k – 1) (3k + 2) = k/(6k + 4) â€¦ (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1/2.5 + 1/5.8 + 1/8.11 + â€¦ + 1/(3k – 1)(3k + 2) + 1/(3k + 3 – 1)(3k + 3 + 2)

= k/(6k + 4) + 1/(3k + 2)(3k + 5)

= [k(3k + 5) + 2] / [2(3k + 2)(3k + 5)]

= (k + 1) / (6(k + 1) + 4)

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 7. 1/1.4 + 1/4.7 + 1/7.10 + â€¦ + 1/(3n – 2)(3n + 1) = n/3n + 1

**Solution:**

Let P (n) = 1/1.4 + 1/4.7 + 1/7.10 + â€¦ + 1/(3n – 2)(3n + 1) = n/3n + 1

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/1.4 = 1/4

Or, 1/4 = 1/4

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1/1.4 + 1/4.7 + 1/7.10 + â€¦ + 1/(3k – 2)(3k + 1) = k/3k + 1 â€¦ (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, [1/1.4 + 1/4.7 + 1/7.10 + â€¦ + 1/(3k – 2)(3k + 1)] + 1/(3k + 1)(3k + 4)

= k/(3k + 1) + 1/(3k + 1)(3k + 4)

= 1/(3k + 1) [k/1 + 1/(3k + 4)]

= 1/(3k + 1) [k(3k + 4) + 1]/(3k + 4)

= 1/(3k + 1) [3k

^{2}+ 4k + 1]/ (3k + 4)= 1/(3k + 1) [3k

^{2}+ 3k + k + 1]/(3k + 4)= [3k(k + 1) + (k + 1)] / [(3k + 4) (3k + 1)]

= [(3k + 1)(k + 1)] / [(3k + 4) (3k + 1)]

= (k + 1) / (3k + 4)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 8. 1/3.5 + 1/5.7 + 1/7.9 + â€¦ + 1/(2n + 1)(2n + 3) = n/3(2n + 3)

**Solution:**

Let P (n) = 1/3.5 + 1/5.7 + 1/7.9 + â€¦ + 1/(2n + 1)(2n + 3) = n/3(2n + 3)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/3.5 = 1/3(2.1 + 3)

or, 1/15 = 1/15

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) = 1/3.5 + 1/5.7 + 1/7.9 + â€¦ + 1/(2k + 1)(2k + 3) = k/3(2k + 3) â€¦ (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1/3.5 + 1/5.7 + 1/7.9 + â€¦ + 1/(2k + 1)(2k + 3) + 1/[2(k + 1) + 1][2(k + 1) + 3]

1/3.5 + 1/5.7 + 1/7.9 + â€¦ + 1/(2k + 1)(2k + 3) + 1/(2k + 3)(2k + 5)

Now putting the value of (i), we get,

= k/3(2k + 3) + 1/(2k + 3)(2k + 5)

= [k(2k + 5) + 3] / [3(2k + 3)(2k + 5)]

= (k + 1) / [3(2(k + 1) + 3)]

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 9. 1/3.7 + 1/7.11 + 1/11.15 + â€¦ + 1/(4n – 1)(4n + 3) = n/3(4n + 3)

**Solution:**

Let P (n) = 1/3.7 + 1/7.11 + 1/11.15 + â€¦ + 1/(4n – 1)(4n + 3) = n/3(4n + 3)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/(3.7) = 1/((4.1 – 1)(4 + 3))

Or, 1/21 = 1/21

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1/3.7 + 1/7.11 + 1/11.15 + â€¦ + 1/(4k – 1)(4k + 3) = k/3(4k + 3) â€¦ (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1/3.7 + 1/7.11 + 1/11.15 + â€¦ + 1/(4k – 1)(4k + 3) + 1/(4k + 3)(4k + 7)

Now putting the value of (i), we get,

= k/(4k + 3) + 1/(4k + 3)(4k + 7)

= 1/(4k + 3) [k(4k + 7) + 3] / [3(4k + 7)]

= 1/(4k + 3) [4k

^{2}+ 7k + 3]/ [3(4k + 7)]= 1/(4k + 3) [4k

^{2}+ 3k + 4k + 3] / [3(4k + 7)]= 1/(4k + 3) [4k(k + 1) + 3(k + 1)]/ [3(4k + 7)]

= 1/(4k + 3) [(4k + 3)(k + 1)] / [3(4k + 7)]

= (k + 1) / [3(4k + 7)]

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 10. 1.2 + 2.2^{2} + 3.2^{3} + â€¦ + n.2^{n} = (n – 1) 2^{n+1} + 2

**Solution:**

Let P (n) = 1.2 + 2.2

^{2}+ 3.2^{3}+ â€¦ + n.2^{n}= (n – 1) 2^{n+1 }+ 2Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1.2 = 0.2

^{0 }+ 2or, 2 = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) =1.2 + 2.2

^{2}+ 3.2^{3}+ â€¦ + k.2^{k}= (k – 1) 2^{k+1}+ 2 â€¦ (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, [1.2 + 2.2

^{2}+ 3.2^{3}+ â€¦ + k.2^{k}] + (k + 1)2k + 1Now, putting the value of (i), we get,

= [(k – 1)2

^{k+1}+ 2] + (k + 1)2^{k+1}= (k – 1)2

^{k+1}+ 2 + (k + 1)2^{k+1}= 2

^{k+1}(k – 1 + k + 1) + 2= 2

^{k+1}Ã— 2k + 2= k.2

^{k+2}+ 2So, P (n) is true for n = k + 1

i.e, P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 11. 2 + 5 + 8 + 11 + â€¦ + (3n â€“ 1) = 1/2 n (3n + 1)

**Solution:**

Let P (n) = 2 + 5 + 8 + 11 + â€¦ + (3n â€“ 1) = 1/2 n (3n + 1)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 2 = 1/2 Ã— 1 Ã— 4

or, 2 = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 2 + 5 + 8 + 11 + â€¦ + (3k â€“ 1) = 1/2 k (3k + 1) â€¦ (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, 2 + 5 + 8 + 11 + â€¦ + (3k â€“ 1) + (3k + 2)

Now, putting the value (i), we get,

= 1/2 Ã— k (3k + 1) + (3k + 2) (using equation (i))

= [3k

^{2}+ k + 2 (3k + 2)] / 2= [3k

^{2}+ k + 6k + 2] / 2= [3k

^{2}+ 7k + 2] / 2= [3k

^{2}+ 4k + 3k + 2] / 2= [3k (k + 1) + 4(k + 1)] / 2

= [(k + 1) (3k + 4)] /2

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 12. 1.3 + 2.4 + 3.5 + â€¦ + n. (n + 2) = 1/6 n (n + 1) (2n + 7)

**Solution:**

Let P (n) = 1.3 + 2.4 + 3.5 + â€¦ + n. (n + 2) = 1/6 n (n + 1) (2n + 7)

Step 1:

Now, let us check P(n) for n=1.

P (1) = 1.3 = 1/6 Ã— 1 Ã— 2 Ã— 9

Or, 3 = 3

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1.3 + 2.4 + 3.5 + â€¦ + k. (k + 2) = 1/6 k (k + 1) (2k + 7) â€¦ (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1.3 + 2.4 + 3.5 + â€¦ + k. (k + 2) + (k + 1) (k + 3)

Now, putting the value (i), we get,

= 1/6 k (k + 1) (2k + 7) + (k + 1) (k + 3) (using equation (i))

= (k + 1) [{k(2k + 7)/6} + {(k + 3)/1}]

= (k + 1) [(2k

^{2}+ 7k + 6k + 18)] / 6= (k + 1) [2k

^{2}+ 13k + 18] / 6= (k + 1) [2k

^{2}+ 9k + 4k + 18] / 6= (k + 1) [2k(k + 2) + 9(k + 2)] / 6

= (k + 1) [(2k + 9) (k + 2)] / 6

= 1/6 (k + 1) (k + 2) (2k + 9)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 13. 1.3 + 3.5 + 5.7 + â€¦ + (2n â€“ 1) (2n + 1) = n(4n^{2} + 6n â€“ 1)/3

**Solution:**

Let P (n) = 1.3 + 3.5 + 5.7 + â€¦ + (2n â€“ 1) (2n + 1) = n(4n

^{2}+ 6n â€“ 1)/3Step 1:

Now, let us check P(n) for n = 1.

P (1) = : (2.1 â€“ 1) (2.1 + 1) = 1(4.1

^{2}+ 6.1 – 1)/3or, 1 Ã— 3 = 1(4 + 6 – 1)/3

or, 3 = 3

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1.3 + 3.5 + 5.7 + â€¦ + (2k â€“ 1) (2k + 1) = k(4k

^{2}+ 6k â€“ 1)/3 â€¦ (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1.3 + 3.5 + 5.7 + â€¦ + (2k â€“ 1) (2k + 1) + (2k + 1) (2k + 3)

Now, putting the value (i), we get,

= k(4k

^{2}+ 6k â€“ 1)/3 + (2k + 1) (2k + 3) (using equation (i))= [k(4k

^{2}+ 6k-1) + 3 (4k^{2}+ 6k + 2k + 3)] / 3= [4k

^{3}+ 6k^{2}â€“ k + 12k^{2}+ 18k + 6k + 9] /3= [4k

^{3}+ 18k^{2}+ 23k + 9] /3= [4k

^{3}+ 4k^{2}+ 14k^{2}+ 14k + 9k + 9] /3= [(k + 1) (4k

^{2}+ 8k +4 + 6k + 6 â€“ 1)] / 3= [(k + 1) 4[(k + 1)

^{2}+ 6(k + 1) -1]] /3So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 14. 1.2 + 2.3 + 3.4 + â€¦ + n(n + 1) = [n (n + 1) (n + 2)] / 3

**Solution:**

Let P (n) = 1.2 + 2.3 + 3.4 + â€¦ + n(n + 1) = [n (n + 1) (n + 2)] / 3

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1(1 + 1) = [1(1 + 1) (1 + 2)] /3

or, 2 = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1.2 + 2.3 + 3.4 + â€¦ + k(k+1) = [k (k + 1) (k + 2)] / 3 â€¦ (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1.2 + 2.3 + 3.4 + â€¦ + k(k + 1) + (k + 1) (k + 2)

Now, putting the value (i), we get,

= [k (k + 1) (k + 2)] / 3 + (k + 1) (k + 2)

= (k + 2) (k + 1) [k/2 + 1]

= [(k + 1) (k + 2) (k + 3)] /3

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 15. 1/2 + 1/4 + 1/8 + â€¦ + 1/2^{n} = 1 â€“ 1/2^{n}

**Solution:**

Let P (n) = 1/2 + 1/4 + 1/8 + â€¦ + 1/2

^{n}= 1 â€“ 1/2^{n}Step 1:

Now, let us check P(n) for n=1.

P (1) = 1/2

^{1}= 1 â€“ 1/2^{1}or, 1/2 = 1/2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = : 1/2 + 1/4 + 1/8 + â€¦ + 1/2

^{k}= 1 â€“ 1/2^{k}â€¦ (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1/2 + 1/4 + 1/8 + â€¦ + 1/2

^{k}+ 1/2^{k+1}Now, putting the value (i), we get,

= 1 – 1/2

^{k}+ 1/2^{k+1}(using eq(i))= 1 – ((2 – 1)/2

^{k+1})So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

### Question 16. 1^{2} + 3^{2} + 5^{2} + â€¦ + (2n â€“ 1)^{2} = 1/3 n (4n^{2} â€“ 1)

**Solution:**

Let P (n) = 1

^{2}+ 3^{2}+ 5^{2}+ â€¦ + (2n â€“ 1)^{2}= 1/3 n (4n^{2}â€“ 1)Step 1:

Now, let us check P(n) for n=1.

P (1) = (2.1 – 1)

^{2}= 1/3 Ã— 1 Ã— (4 – 1)or, 1 = 1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1

^{2}+ 3^{2}+ 5^{2}+ â€¦ + (2k â€“ 1)^{2}= 1/3 k (4k^{2}â€“ 1) â€¦ (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1

^{2}+ 3^{2}+ 5^{2}+ â€¦ + (2k â€“ 1)^{2}+ (2k + 1)^{2}Now, putting the value (i) ,we get,

Or, 1/3 k (4k

^{2}â€“ 1) + (2k + 1)^{2}(using eq(i))= 1/3 k (2k + 1) (2k â€“ 1) + (2k + 1)

^{2}= (2k + 1) [{k(2k – 1)/3} + (2k + 1)]

= (2k + 1) [2k

^{2}â€“ k + 3(2k + 1)] / 3= (2k + 1) [2k

^{2}â€“ k + 6k + 3] / 3= [(2k + 1) 2k

^{2}+ 5k + 3] /3= [(2k + 1) (2k(k + 1)) + 3 (k + 1)] /3

= [(2k + 1) (2k + 3) (k + 1)] /3

= (k + 1)/3 [4k

^{2}+ 6k + 2k + 3]= (k + 1)/3 [4k

^{2}+ 8k â€“ 1]= (k + 1)/3 [4(k + 1)

^{2}â€“ 1]So, P (n) is true for n = k + 1

i.e., P (n) is true for all n âˆˆ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n âˆˆ N.

## Please

Loginto comment...